Community-Based Participatory Research in Diabetes Prevention Programs - Raihan K Khan; Ranjita Misra (Shahid Beheshti University of Medical Sciences, 2019)
The purpose of this study was to determine how community-based diabetes prevention programs utilized the concept and contents of the Community Based Participatory Research approach. PubMed was used to search and extract peer reviewed articles that included words Community-Based Participatory Research, and Diabetes in the title, abstract or in the main article. Initially 243 articles were identified and after the final screening, a total of 38 articles were selected for review. An advisory board was mentioned in most of the articles that worked on planning and reviewing the study protocol. However, the review found lack of inclusion of the advisory board in data analysis and study result dissemination process. Furthermore, majority of the studies were found be conducted in North America. The concept of Community Based Participatory Research should be followed at each step of a community-based diabetes prevention program. This approach should also be widely adopted globally.